Financial Distress in Palm Oil Firms: Leverage, Growth, and Profitability as Key Drivers - Rahma Adinda Trihapsari; Riyanti Riyanti (Jurnal RAK (Riset Akuntansi Keuangan), 2025)
Indonesia's palm oil sector is significant due to its volatility and fluctuations in global prices and operating costs. This study analyzes the impact of leverage, revenue growth, and profitability on the volatile financial situation of palm oil companies listed on the Indonesian stock exchange (2020–2024). Using quantitative association analysis and objective sampling, eight companies (40 observations) were examined using multiple linear regression analysis (EViews 12). The results suggest that companies have excellent start-up and profitability with a significant positive impact on Z-scores, resulting in higher financial gains and a low rate of insolvency. Sales growth, on the other hand, has a negligible negative impact. Theoretically, this study supports the principal-agent theory and suggests that strategic debt and profit management minimize agency costs and ensure stability in the agricultural sector. Therefore, effective capital management and optimal use of resources are crucial for mitigating financial risk.